Reactivating fear memory under propranolol resets pre-trauma levels of dendritic spines in basolateral amygdala but not dorsal hippocampus neurons - Vetere, Gisella; Piserchia, Valentina; Borreca, Antonella; Novembre, Giovanni; Aceti, Massimiliano; Ammassari-Teule, Martine (Frontiers in Behavioral Neuroscience, 2013)
Fear memory enhances connectivity in cortical and limbic circuits but whether treatments disrupting fear reset connectivity to pre-trauma level is unknown. Here we report that C56BL/6J mice exposed to a tone-shock association in context A (conditioning), and briefly re-exposed to the same tone-shock association in context B (reactivation), exhibit strong freezing to the tone alone delivered 48 h later in context B (long term fear memory). This intense fear response is associated with a massive increase in dendritic spines and phospho-Erk (p-ERK) signalling in basolateral amygdala (BLA) but neurons. We then show that propranolol (a central/peripheral β-adrenergic receptor blocker) administered before, but not after, the reactivation trial attenuates long term fear memory assessed drug free 48h later, and completely prevents the increase in spines and p-ERK signalling in BLA neurons. An increase in spines, but not of p-ERK, was also detected in the dorsal hippocampus (DH) of the conditioned mice. DH spines, however, were unaffected by propranolol suggesting their independence from the ERK/β-ARs cascade. We conclude that propranolol selectively blocks dendritic spines and p-ERK signalling enhancement in the BLA; its effect on fear memory is, however, less pronounced suggesting that the persistence of spines at other brain sites decreases the sensitivity of the fear memory trace to treatments selectively targeting β-ARs in the BLA.